Solvent Polarity Effect on The Electronic Spectra of Laser Dye (P- Terphenyl Molecule ) (Journal of the College of Basic Education, 2022)
The aim of this study is to investigate the effects of solvents of various polarities on the electronic spectra(absorption and fluorescence) of p-terphenyl dye at room tempreture with concentrations 10-4M , 10-5M. The singlet state excited dipole moments and ground state dipole moments were estimated from the equations of Lippert and Bakshiev -Kawski and Chamma -Viallet using the variation of Stokes shift along with the solvent’s dielectric constant (Ɛ) and refractive indices (n). It was observed that excited state dipole moments were found to be larger than the ground state ones. That indicates the redistribution of electronic charge densities had been occured. Also, the experimental variations in the dipole moment values can be explains in terms of their possible resonance structures.